The Hallmarks of Endometriosis - Psilopatis, Iason; Burghaus, Stefanie; Au, Katharina; Hofbeck, Louisa; Windischbauer, Lisa; Lotz, Laura; Beckmann, Matthias W. (Geburtshilfe und Frauenheilkunde, 2024)
A heuristic tool called “the hallmarks of cancer” helps to reduce the enormous complexity of cancer phenotypes and genotypes to a preliminary set of guiding principles. Other aspects of cancer have surfaced as possible improvements in our understanding of the disease’s mechanisms. Endometriosis is a gynecological disease condition negatively impacting the quality of life of many women. To date, there is no curative treatment for endometriosis. Therapy is aimed at treating the symptoms using hormone therapy, pain therapy and complementary therapy. Chronic pain and overlapping pain syndromes and illnesses can also be treated with multimodal pain therapy and psychosomatic therapy. Endometriosis is, however, a chronic and complex entity which, in this regard, resembles cancer. The present work investigates the hallmarks of endometriosis with a view to summarizing the current research status and paving new ways for future research projects.
Keywords: endometriosis; genetics; epigenetics; molecular; signaling; pathway